(untitled) (مجلة الواحات للبحوث والدراسات, 2023)
ملخص: يدرس المقال في رواية "أنا وحاييم" للحبيب السايح تشكل مفهوم الهوية الوطنية التي ظلت تتأثر بالكثير من المؤثرات خلال عملية التبلور. ونسلط الضوء على بعض المقومات التي أُغفلت تاريخيا، تلك التي تتأسس عليها الهوية القوية والتي تنبني عليها الأوطان في إطار مشروع مجتمع ينهض بالدولة، ويحكم سلطتها على أسس اجتماعية وثقافية وفكرية متينة. كما يتناول المقال بالدراسة وجوب إعادة النظر في تاريخ ثورة التحرير الجزائرية ووجب كتابة تاريخها من قبل المتخصصين لا السياسيين، من منظور الروائي على الأقل، وإشراك النخبة المثقفة في القراءة والكتابة حتى لا نكرر أخطاء الماضي بغية إرساء قواعد ديمقراطية صحيحة . كلمات دالة: هوية، تاريخ، ثورة تحريرية، رواية Abstract: In The Novel "I And Haim" By Habib Sayeh, The Article Examines The Formation Of The Concept Of National Identity, Which Has Been Influenced By Many Influences During The Process Of Maturation. We Highlight Some Of The Elements That Have Been Neglected Historically, Those On Which A Strong Identity Is Based And On Which Nations Are Built Within The Framework Of A Community Project That Advances The State And Governs Its Authority On Solid Social, Cultural And Intellectual Foundations. The Article Also Deals With The Study That The History Of The Algerian Liberation Revolution Must Be Reconsidered And That Its History Must Be Written By Specialists, Not Politicians, From The Perspective Of The Novelist At Least, And To Involve The Educated Elite In Reading And Writing So As Not To Repeat The Mistakes Of The Past In Order To Establish Correct Democratic Rules. Key Words: Identity, History, Editorial Revolution, Novel.